ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN SINGLE INDEX MODEL UNTUK PROYEKSI INVESTASI PADA SAHAM INDEKS LQ45 DI BURSA EFEK INDONESIA - Syam, Sadriani; Rauf, Anwar; Musa, Chalid Imran (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this study is to determine the composition of stocks forming the optimal portfolio with a single index model on the LQ45 Index stock, so that the stocks that are used as investment choices or form a portfolio are obtained. The population of this study is all the shares of issuers or go public companies that are in the LQ45 Index on the Indonesia Stock Exchange for the period February 2017-January 2021, which are 66 company shares while the sample of this study is 65 company shares which were selected based on non-probability sampling technique with the method purposive sampling. Data collection is done by using documentation techniques. Data analysis was carried out with the single index model stage, starting with collecting monthly closing price data to obtain the optimal portfolio and then measuring the optimal portfolio performance from the single index model. Based on the analysis results, there are 18 stocks that make up the optimal portfolio including MDKA, ANTM, TKIM, INKP, BRPT, ERAA, ACES, TBIG, CPIN, TPIA, BBCA, INCO, MEDC, MYRX, INDY, TOWR, MIKA, and BBRI stocks with expected returns the portfolio that investors will receive is 3.35% per month with portfolio risk (portfolio variance of 0.26% per month and standard deviation of 5.11% per month). From the results of the measurement of the optimal portfolio performance formed using the Sharpe Index, the optimal portfolio performance is 0.0690 or 6.90%. If using the Treynor Index, the optimal portfolio performance is 0.0130 or 1.30%. Meanwhile, if using the Jensen Index, the optimal portfolio performance is 0.0061 or 0.61%.